Pengaruh Managerial Ownership, Company Growth, Investment Opportunity Set, dan Debt Covenant terhadap Konservatisme Akuntansi - Manulu, Raja Vanaldo Boang; Fiana, Okta (Program Studi Manajemen Universitas Muhadi Setiabudi, 2023)
This study aims to determine the influence of managerial ownership, company growth, investment opportunity set, and debt covenant on accounting conservatism in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2021. This research uses a quantitative approach. The sampling technique uses a non-probability sampling method for the type of sampling is purposive sampling. The population in this study includes thirtytwo manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2021. The data analysis method used is panel data regression analysis. The results of this study show that simultaneously managerial ownership, company growth, investment opportunity set, and debt covenant have a significant effect on accounting conservatism. The results of the panel data regression test can partially be seen that company growth and investment opportunity set have proven to have a positive and significant effect on accounting conservatism. While managerial ownership and debt covenants have a negative and significant effect on accounting conservatism.